Theory of a practice: A foundation for Blumenberg's metaphorology in Ricoeur's theory of metaphor. (December 2019) - Hawkins, Spencer
Hans Blumenberg is celebrated for demonstrating that metaphors have had a more foundational influence than concepts on European intellectual history. Many acknowledge that his insights might have achieved even greater impact if he had articulated a more explicit theory of metaphor. In 1960 Blumenberg discusses the historical formation of metaphors that have given rise to meaningful discourses on metaphysical abstractions, like God, existence, or Being, but he does not develop a general model of metaphoric language, and his work rarely engages with other contemporary theories of metaphor. During Blumenberg's lifetime, French and German postwar philosophers rarely cited one another. Yet French hermeneutics, and the work of philosopher Paul Ricoeur in particular, may have strongly influenced Blumenberg's research group, Poetik und Hermeneutik . This paper is an attempt to recuperate intellectual affinities between Blumenberg and Ricoeur, in order to demonstrate that Ricoeur's claims about metaphor provide the theoretical background for a fuller appreciation of Blumenberg's metaphor analyses.